2011
DOI: 10.1016/j.applanim.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the effects of providing straw at different stages of life on tail-biting and other behaviour in commercially housed pigs

Abstract: Tail-biting (TB) is a welfare concern. Recent studies indicate that early provision of straw may help prevent TB, however, many of these studies were carried out on small groups of pigs and may have limited applicability to commercial farms. The effect of providing straw at different stages of life was studied in large groups of pigs (21-39) on a commercial farm. Six replicates of four treatments were used (No Straw (NS), Straw in Finishing (12 weeks of age onwards) (SF), Straw from Weaning (SW), Straw Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Where pigs receive manipulable materials during the grower stage, past housing experience makes little difference to tail manipulation behaviours (Day et al, 2002; no tail damage reported, Simonsen, 1995;Statham et al, 2011). However, a greater risk of tail lesions caused by tail biting occurs in pigs which have experienced manipulable materials in the farrowing pen early in life, but which are then absent during later stages (Ruiterkamp, 1985;Munsterhjelm et al, 2009).…”
Section: Risk Factors For Tail Biting Which Are Characteristics Of Thmentioning
confidence: 99%
“…Where pigs receive manipulable materials during the grower stage, past housing experience makes little difference to tail manipulation behaviours (Day et al, 2002; no tail damage reported, Simonsen, 1995;Statham et al, 2011). However, a greater risk of tail lesions caused by tail biting occurs in pigs which have experienced manipulable materials in the farrowing pen early in life, but which are then absent during later stages (Ruiterkamp, 1985;Munsterhjelm et al, 2009).…”
Section: Risk Factors For Tail Biting Which Are Characteristics Of Thmentioning
confidence: 99%
“…A previous study has shown that teeth clipping may not be routinely necessary for some modern pig rearing systems (Bates, Hoge, Edwards, & Straw, ). In addition, tail docking is conducted routinely to prevent tail biting in pigs, but it does not completely eliminate tail biting (Hunter et al, ), especially when pigs are housed in high density and barren environments (Amdi et al, ; Statham, Green, & Mendl, ). Tail docking could cause traumatic neuromas and chronic infection (Herskin, Thodberg, & Jensen, ; Sandercock, Smith, Giminiani, & Edwards, ).…”
Section: Introductionmentioning
confidence: 99%
“…withdrawal of straw from pigs (Statham et al 2011)) then these may have been more pronounced in those replicates that received the objects earlier in the 5-week study period. The complexity condition did not experience addition and withdrawal of different types of object, and also showed no effect of replicate.…”
Section: Discussionmentioning
confidence: 99%